Pelatihan Manajemen Kepemimpinan (Leadership) Siswa Dalam Berorganisasi di MA Miftahul Ulum Sukaoneng - Sholihan; Wati, Riya; Aisiyah, Safitri; Ariyani; Ariyana (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This community service focuses on the issue of students' lack of understanding regarding the importance of leadership, discipline, and the fundamentals leadership principles. The aim of this community service program is to enhance students' ability to lead themselves, develop discipline, and improve their communication and adaptation skills within the school organization (OSIS). The training aploys is an active learning approach with lectures and question-and-answer sessions. The results of this service show that leadership training can enhance the abilities of MA Miftahul Ulum Sukaoneng students in leading themselves and others, building a strong personal character, fostering discipline in time management, and improving communication and adaptation skills within the organization. This training has a positive impact on students' leadership skills, effective communication, discipline, team building, and self-confidence.